2018
DOI: 10.1016/j.joca.2018.02.900
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intra-articular glucocorticosteroids and exercise on symptoms and bone marrow lesions in knee osteoarthritis: a secondary analysis of results from a randomized controlled trial

Abstract: EudraCT number: 2012-002607-18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…37 Similarly to our study, a randomized controlled superiority trial indicated that an intra-articular injection of 40 mg methylprednisolone plus exercise did not increase the size of knee BML over 26 weeks, and the therapy even decreased the size of knee BML over 14 weeks, compared with placebo plus exercise. 41 While the route of injection of methylprednisolone differs (intra-articular versus intravenous), this combined with our data supports that the administration of methylprednisolone does not have a detrimental effect on the size of osteoarthritis-related BML.…”
Section: Discussionsupporting
confidence: 77%
“…37 Similarly to our study, a randomized controlled superiority trial indicated that an intra-articular injection of 40 mg methylprednisolone plus exercise did not increase the size of knee BML over 26 weeks, and the therapy even decreased the size of knee BML over 14 weeks, compared with placebo plus exercise. 41 While the route of injection of methylprednisolone differs (intra-articular versus intravenous), this combined with our data supports that the administration of methylprednisolone does not have a detrimental effect on the size of osteoarthritis-related BML.…”
Section: Discussionsupporting
confidence: 77%
“…To date, intra‐articular delivery has been a widely accepted therapeutic method for the treatment of OA. In addition to the traditional drugs such as corticosteroids and hyaluronic acid (Nielsen et al, 2018; Smith et al, 2019), researchers are developing new drugs with anti‐inflammatory and cartilage‐protective functions (Alves et al, 2020; Garza et al, 2020; Nemirov et al, 2020), and as part of this development, circRNA injection has been used in some OA animal models. Our previous study (Zhou et al, 2019) showed that circRNA.33186, which was significantly upregulated in in vivo and in vitro OA mouse model, regulated ECM catabolism and chondrocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, intra-articular delivery has been a widely accepted therapeutic method for the treatment of OA. In addition to the traditional drugs such as corticosteroids and hyaluronic acid (Nielsen et al, 2018;Smith et al, 2019) OA animal models. Our previous study (Zhou et al, 2019) showed that circRNA.33186, which was significantly upregulated in in vivo and in vitro OA mouse model, regulated ECM catabolism and chondrocyte apoptosis.…”
Section: Mir-296-3p Directly Targets Ptenmentioning
confidence: 99%
“…К 26 неделе различия были нивелированы (0,8%, p = 0,65]. Авторы сделали заключение, что эти результаты -доказательство малой силы наличия зависимости между внутрисуставным применением глюкокортикостероидов и динамикой ОКМ [39]. Регулярное внутрисуставное введение триамцинолона или плацебо раз в три месяца на протяжении двух лет (8 инъекций) у 140 пациентов приводило к значительно большей потере объема хряща в группе триамцинолона (-0,21 мм), чем в группе физиологического раствора (-0,1 мм) при отсутствии различий по влиянию на суставную боль [40].…”
Section: влияние консервативной терапии на отек костного мозгаunclassified